Decentralised meta-scheduling strategy in Grid environments. (6th August 2009) - Pop, Florin; Cristea, Valentin
The paper presents the communication model for decentralised meta-scheduler in Grid environments. The proposed model is a distributed, fault-tolerant, adaptive and efficient one. It is designed as an agent's platform for Grid scheduling algorithms, which denote the decentralised architecture of this model. The platform contains two types of agents: one for resource management (Broker) and the other manages the users tasks requests (Agents). The paper describes the communication protocol between agents and the proposed structure for agents. It is presented the description of the scheduling algorithm in a logical flow of activities. The scheduler uses cluster schedulers like Condor or PBS, which denote the meta-scheduler approach. The agents' platform and the scheduling algorithm are tested in a cluster mode. The results highlight very good communication time and according with multiple users' requests.